Scaling out Climate Smart Agriculture: Strategies and Guidelines for Smallholder Farming in Western Kenya - Schaller, Michaela; Barth, Elena I.; Blies, Darinka; Röhrig, Felicitas; Schümmelfeder, Malte (SLE Postgraduate Studies on International Cooperation for Sustainable Development, 2017)
BACKGROUND The GIZ Advisory Service for Agricultural Research and Development (BEAF) in cooperation with GIZ Western Kenya and the Centre for Tropical Agriculture in Nairobi (CIAT) commissioned the Centre for Rural Development (SLE) to carry out this study. Kenya is a focus country of the German Federal Ministry for Economic Cooper-ation and Development (BMZ) SEWOH Initiative (One World, No Hunger), with GIZ as one of the implementing partners. Two SEWOH components are imple-mented in Western Kenya: soil protection and rehabilitation for food security and green innovation centres for the agricultural and food sector. Both projects show strong links to the concept of Climate Smart Agriculture (CSA). As part of the Consultative Group on International Agricultural Research (CGIAR), CIAT focuses on applied research on CSA. The study contributes to the development of strategies and guidelines to pro-mote the adoption of CSA techniques by smallholders in Western Kenya, i.e., in the counties of Siaya and Kakamega. BASIC SOCIO-ECONOMIC DATA ON KENYA With a Human Development Indicator (HDI) of 0.548, Kenya ranks 145th in the world (UNDP, 2015). Approximately 65% of Kenya’s population is employed in the agricultural sector. This showcases the tremendous significance agriculture holds for key issues at the heart of development: food security, poverty reduction, sus-tainable livelihoods. Kenya is a youthful country, where roughly half the population is 18 years of age or younger. Youth is concentrated in the rural areas, while their proportion in urban areas is significantly lower. Data from 2009 shows that almost 50 per cent of the population (45.2%) lives below the poverty line defined by the World Bank. Of the 38 million people in Kenya, 4.7 million are primarily engaged in small-scale agriculture and pastoral activities. The Kenyan population is unevenly distributed, with densities substantially higher in the central region around Nairobi and in Western Kenya (Wiesmann et al., 2014).